The 2022 India Report Card on physical activity for children and adolescents - Jasmin Bhawra; Anuradha Khadilkar; Ghattu V. Krishnaveni; Kalyanaraman Kumaran; Tarun R. Katapally (Journal of Exercise Science & Fitness, 2023)
Background/Objective: With strong evidence of physical inactivity's link to chronic disease and economic burden – particularly with childhood active living behaviors tracking into adulthood – it is imperative to promote physical activity among children and adolescents in India. Objectives: To evaluate active living patterns among Indian children and adolescents. Methods: The India Report Card (IRC) team, which consists of experts in India and Canada, systematically collected and appraised evidence on 11 indicators of active living, including 5 behavioral (Overall Physical Activity, Organized Sport Participation, Active Play, Active Transportation, Sedentary Behavior), 2 individual-level (Physical Fitness, Yoga) and 4 sources of influence (Family and Peers, School, Community and Built Environment, Government). Peer-reviewed articles were appraised based on national representativeness, sample size, and data quality. Grey literature was appraised based on comprehensiveness, validity of the sources, and representativeness. All indicators were assessed against parameters provided by the Active Healthy Kids Global Alliance. Results: Active Transportation and Government Strategies were ranked highest with a B- and C+ grade, respectively. Overall Physical Activity and Schools were assigned a C grade, while Sedentary Behavior and Community and Built Environment were given D grades. Yoga was the lowest ranking indicator with a D- grade. Organized Sport Participation, Active Play, Family and Peers, and Physical Fitness were all graded incomplete. Conclusions: Active Transportation, Government Strategies, and Overall Physical Activity have improved since the 2018 IRC, a positive trend that needs to be translated to other indicators. However, Sedentary Behavior has consistently worsened, with grades C, C-, and D-, in 2016, 2018, and 2022, respectively. Evidence generated by the 2022 IRC suggests opportunities for improvement not only in India, but also the 56 other countries taking part in Global Matrix 4.0.